An Entry to Double Phosphanyl‐Bridged Dinuclear Rhodium(II) Complexes. Issue 21 (15th May 2019) - Böttcher, Hans‐Christian; Graf, Marion; Mayer, Peter; Scheer, Manfred
Abstract : The reaction of [RhCp(coe)2 ] (1, coe = cis ‐cyclooctene) with one equivalent of the secondary phosphines PR2 H in refluxing toluene afforded in situ the new complexes [RhCp(coe)(PR2 H)] (R = Ph, 2a ; R = o ‐tolyl, 2b ; R = t Bu, 2c ) in good yields. Further thermolysis of 2a and 2b, respectively, in refluxing xylene resulted in the formation of the dinuclear doubly phosphanyl‐bridged rhodium(II) species [{RhCp(µ‐PR2 )}2 ] (3a and 3b ). This thermolytic approach does not work in the case of 2c since the t Bu substituents increase the electron density on the rhodium center and impede, therefore, the loss of the olefinic ligand presumably caused by a stronger back donation effect. On the way from 2a to 3a the intermediate rhodium(III) complex [{RhCp(µ‐PPh2 )(H)2 }2 ] (4a ) was isolated. All new compounds were fully characterized by spectroscopic methods as well as by X‐ray crystallography in the case of 3a, 3b and 4a confirming their molecular structures in the crystal. The compound [{RhCp(µ‐PPh2 )}2 ] did not react with dihydrogen at ambient conditions and not even in refluxing toluene affording the complex 4a by oxidative addition as originally assumed. Abstract : A synthesis affording the phosphanyl‐bridged rhodium complexes [{RhCp(µ‐PR2 )}2 ] (R = Ph, 3a ; R = o ‐tolyl, 3b ) was developed. The procedure started from [RhCp(coe)2 ] reacting with equimolar amounts of the corresponding phosphine PR2 H in refluxing xylene. In the first step, [RhCp(coe)(PR2 H)] as the intermediate species were detected. During the synthesis of 3a, the complex [{RhCp(µ‐PPh2 )(H)}2 ] (4a ) could be isolated as a further intermediate. The molecular structures of the compounds 3b and 4a in the crystal were confirmed by X‐ray crystallography.